Length-Weight Relationship and Growth Condition of Mystus gulio (Ham.) in Different Months and Sexes - Begum, M; Pal, HK; Islam, MA; Alam, MJ (University Journal of Zoology, Rajshahi University, 2010)
Key words: Length-weight relationship; growth condition; Mystus gulio DOI: 10.3329/ujzru.v28i0.5292 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 73-75